The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/sea2.12281
|View full text |Cite
|
Sign up to set email alerts
|

The “Department of Human Needs”: Renewable energy and the water–energy–land nexus in Zanzibar

Abstract: In designating its Sustainable Development Goals (SDGs), the United Nations invoked the “water–energy–land (WEL) nexus” to emphasize the interconnections between different policy sectors and accentuate the importance of an integrated approach to human and environmental welfare. Identifying the WEL nexus draws attention to the interplay of technical and moral values, the intersections or overlaps between these values, and the areas where values conflict, tradeoffs happen, and priorities are set or shifted. And … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In reflecting on our discussions at the Annual Meeting of the 2022 Society for Economic Anthropology as well as on the articles collected in the following pages, we suggest that there are at least six ways we can become more precise with value theory: In considering the ethical and ontological presuppositions that always precede the ascription of value (Field, 2023; Rivers, 2023); In taking seriously the affordances that various qualia provide to specific things when they become valued (Graber, 2023); In noting how the relationships that underscore value ascriptions shift when people find themselves relating not to other people but rather to imaginary social totalities such as states or national communities (Majeed, 2023; Phillips, 2023); In appreciating the weird ways that value ascriptions are often sticky despite the best wishes of a given group of people (Majeed, 2023; Phillips, 2023); In accepting how value ascriptions are often retrospective and infused with certain claims about what the past was like (Khorasani, 2023); and In reckoning with the fact that humans often occupy multiple contradictory value regimes at the same time (Dean, 2023; DuBois, 2023). …”
Section: What's It Worth To You?mentioning
confidence: 99%
See 3 more Smart Citations
“…In reflecting on our discussions at the Annual Meeting of the 2022 Society for Economic Anthropology as well as on the articles collected in the following pages, we suggest that there are at least six ways we can become more precise with value theory: In considering the ethical and ontological presuppositions that always precede the ascription of value (Field, 2023; Rivers, 2023); In taking seriously the affordances that various qualia provide to specific things when they become valued (Graber, 2023); In noting how the relationships that underscore value ascriptions shift when people find themselves relating not to other people but rather to imaginary social totalities such as states or national communities (Majeed, 2023; Phillips, 2023); In appreciating the weird ways that value ascriptions are often sticky despite the best wishes of a given group of people (Majeed, 2023; Phillips, 2023); In accepting how value ascriptions are often retrospective and infused with certain claims about what the past was like (Khorasani, 2023); and In reckoning with the fact that humans often occupy multiple contradictory value regimes at the same time (Dean, 2023; DuBois, 2023). …”
Section: What's It Worth To You?mentioning
confidence: 99%
“…Erin Dean (2023), in her article on resource management in Zanzibar, develops the idea of a “resource nexus” to theorize what happens when humans try to institutionalize and manage contradictory value demands. Her case describes Zanzibar's Ministry of Land, Housing, Water, and Energy, what she calls the “Department of Human Needs.” Rather than identifying a winner or a loser in the competing priorities held by such a multimodal government agency, she suggests that we can instead identify numerous possible futures: “the possible extension of a colonial mentality that includes control of nature, opportunistic extraction, and increasing inequality; but also the possibility for cooperative creation, holistic livability, and systemic transformation” (2023, 253). For the Department of Human Needs, it is not so much one future or another, but rather many, and all at the same time.…”
Section: Into the Value‐versementioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of the resource system allows the identification of effective policies for improving adaptive capacity [15,16]. For instance, previous research in Zanzibar identified solar as an important energy transition to disentangle from expensive dependencies for electricity from mainland Tanzania and ensure consistent pumping of water [17]. An integrated approach to exploring resource security across sectors could, therefore, potentially better inform where priorities are set and shifted.…”
Section: Introductionmentioning
confidence: 99%